Les interactions entre eau douce et eau marine : étude des risques potentiels et modalités de gestion - Jérôme Longuepée; Olivier Petit (Territoire en Mouvement)
This article deals with the way hazards, resulting from the interactions between fresh and marine waters in coastal zones, lead to question the variety of management practices of natural resources and the environment. In a first step, we underline the bidirectional character of hazards driven by fresh and marine waters in coastal areas. We discuss, in a second step, two way of dealing with integrated management of natural resources in those areas: namely Integrated Coastal Zone Management (ICZM) and the Integrated Water Resources Management (IWRM). While it is easy to recognize a convergence in the philosophy of such processes, we stress the necessity to go beyond distinctions, in order to build a more comprehensive approach. Finally, with the example of the Wateringues territory, located in the North of France, we illustrate the stakes of an integrated approach, in an area characterized by multiple pressures, where use conflicts are sometimes strengthened by the presence of hazards.